1978
DOI: 10.1038/bjc.1978.278
|View full text |Cite
|
Sign up to set email alerts
|

Clinical response and plasma levels of 5-fluorouracil in patients with colonic cancer treated by drug infusion

Abstract: Summary.-Concentrations of 5-fluorouracil (FU) were measured in the plasma of patients receiving i.v. infusions of the drug for 5 days as treatment for adenocarcinoma of the gastrointestinal tract. Concentrations of FU varied widely in many patients. Concentration of drug x time of infusion (C x t values) were calculated.Patients showing a partial response or stabilization of disease had significantly higher C x t values than non-responders. Methyl CCNU did not affect the C x t values of FU. Determination of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 6 publications
2
27
0
Order By: Relevance
“…When available, data showed values up to 15 times higher than the normal concentrations expected at our institute and, in most cases, above the plasma concentrations associated with toxicities. 31 Interestingly, patient P18 had an apparent normal DPD function but presented with cutaneous eruption and sepsis after 5-FU-CDDP infusion; 5-FU assay results on that patient showed a 5-FU Css far below the toxic threshold, suggesting that the side effects observed in that patient were not related to the 5-FU intake. More surprisingly, patient P5, also displaying a normal U/UH2 ratio, was found to have elevated 5-FU plasma concentrations.…”
Section: Discussionmentioning
confidence: 90%
“…When available, data showed values up to 15 times higher than the normal concentrations expected at our institute and, in most cases, above the plasma concentrations associated with toxicities. 31 Interestingly, patient P18 had an apparent normal DPD function but presented with cutaneous eruption and sepsis after 5-FU-CDDP infusion; 5-FU assay results on that patient showed a 5-FU Css far below the toxic threshold, suggesting that the side effects observed in that patient were not related to the 5-FU intake. More surprisingly, patient P5, also displaying a normal U/UH2 ratio, was found to have elevated 5-FU plasma concentrations.…”
Section: Discussionmentioning
confidence: 90%
“…There are also studies suggesting a relationship between the plasma clearance or AUC offluorouracil and antitumour response. These studies, however, contain only a small number of patients and the results have not been confirmed in larger series (Hillcoat et al 1978;Seitz et al 1983). It has also been shown that there is no relationship between the plasma pharmacokinetics of fluorouracil and the cellular concentration of its metabolites (Finan et al 1987).…”
Section: Fluorouracilmentioning
confidence: 95%
“…In the 1970s, Hillcoat et al reported on the close correlation between 5-FU plasma drug concentrations and tumor response in patients with gastrointestinal tract (GI) cancers [18]. In this study, patients received 5-day continuous infusion of 5-FU at a dose of 1200 mg/m 2 /day on days 1–5 in combination with the nitrosourea CCNU 150 mg/m 2 on day 1, and this combination regimen was administered every 6 weeks.…”
Section: Existence Of Pk-pd Relationshipsmentioning
confidence: 99%